An amended low-cost indirect MPPT strategy with a PID controller for boosting PV system efficiency - Abdelkhalek Chellakhi; Said El Beid; Mouncef El Marghichi; El Mahdi Bouabdalli (Results in Engineering)
Operating a photovoltaic (PV) array at its optimum power point (MPP) despite fluctuating weather conditions is challenging. However, tracking this point enhances system efficiency and energy yields. Various maximum power point tracker (MPPT) techniques have been developed, differing in convergence speed, tracking efficiency, and implementation complexity. The Incremental Conductance (IC) strategy is popular due to its simplicity and reliability, but its fixed perturbation step size results in low tracking efficiency, MPP fluctuation, high power loss, and poor performance. This study proposes an improved IC (IMP-IC) method using indirect control based on a PID controller with an adjustable step size. The IMP-IC approach is simple, cost-effective, and implementable using a low-cost ATmega328 microcontroller on the Arduino Uno board.Simulations in the Proteus environment compared its performance to other MPPT techniques like conventional IC, zone voltage (ZV), fuzzy logic (FL), and novel adjustable step InC (NAS-INC). Results under various weather conditions, including rapid changes and EN50530 testing standards, indicate the IMP-IC approach outperforms existing methods. Specifically, it achieved an average tracking time of 0.12 seconds and tracking efficiencies of 99.40 % (static) and 99.88 % (dynamic). The IMP-IC method showed negligible power losses and fluctuations, a quick convergence speed and significantly lower implementation complexity. These attributes position the IMP-IC method as an effective solution for enhancing the reliability and performance of PV systems.